A “Ticking Bomb” Named FSO Safer: Environmental Impact and State Responsibility under the View of International Law of the Sea - Gregory Joshua Manogar (Padjadjaran Journal of International Law, 2022)
Oil spill is known as one of many common environmental disasters. Many oil spill disasters have cost countries and companies around the world huge amount of losses, and most importantly severe environmental damage which is not recoverable. Currently, one of Yemeni ships named FSO Safer is trapped and stranded around 5 miles from the outer coast of Yemen. The ship is carrying around 1 million barrels of crude oil in its storage, unfortunately the ship is currently in a poor condition and unstable, which may cause the largest super tanker oil spill disaster in the history, even worse than the Exxon Valdez disaster. Countries around the world including UN Members are looking for an immediate alternative to mitigate the disaster, as the Yemeni Government is currently in an armed conflict with the Houthi and have a very limited resource. This paper will analyze, which country will be affected by this imminent peril, who shall be responsible for the disaster and whether an exceptional circumstance that surrounds Yemen Government may discharge them for their responsibility as a state. This paper found that, this imminent disaster, will affect most of the countries located in the area of Red Sea, and the responsibility to deal with this imminent disaster are attached to all the affected countries under the UNCLOS 1982, including Yemen without any exception. An international movement initiated by the UN and Yemen Government itself must act immediately to prevent the disaster.